Fractal dimension in the evaluation of different treatments of muscular injury in rats - Garcia, Thiago Alves; Tamura Ozaki, Guilherme Akio; Castoldi, Robson Chacon; Koike, Tatiana Emy; Trindade Camargo, Regina Celi [UNESP]; Silva Camargo Filho, José Carlos [UNESP] (Elsevier, 2018)
Objectives: To evaluate alterations from different therapies in muscular injury using the Fractal Dimension (FD) method. Methods: 35 animals were allocated in Control Group (C), Injury Control Group (IC), Injury Low Level Laser Therapy Group (ILT), Injury Platelet Rich Plasma Group (IP), and Injury LLLT and PRP Group (ILP). The animals suffered a stretch injury in gastrocnemius muscle and after that IP and ILP groups received PRP application. The ILT and ILP groups received daily LLLT applications for seven days. After seven days the animals were euthanized and the gastrocnemius muscle removed and frozen. The muscles were stained with Hematoxylin and Eosin (HE) and Picrosirius Red, for observation of the morphology of the injury and semi-quantitative and quantitative analysis through the Fractal Dimension (FD) method. Results: In the qualitative and semi-quantitative analysis, in relation to IC group, the ILT presented a reduction in rounded fibers and the IP in angular fibers. The ILP group demonstrated a reduction in both polymorphic fibers and inflammatory infiltrate. The FD of the muscles stained with HE was higher in the groups that suffered the injury when compared to the C group (p < 0.05); the FD of the collagen demonstrated no statistical difference between the groups. Conclusion: Both treatments were able to accelerate injury repair, and the association of both presented better results than the isolated applications. However, the FD method showed no sensitivity to differentiate the treatments, either in the histological aspects or the injury in collagen.
Keywords: Collagen; Fractal dimension; Histology; Low level laser therapy; Platelet rich plasma